Biomechanical conditions for stabilizing quadruple figure skating jumps as a process of optimization - Knoll, Ka.; Härtel, T. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
Recent investigations of the stabilization of quadruple jumps in figure skating have shown that an efficiency oriented optimization of the jump technique is needed. In this process the biomechanical possibilities for a big angular momentum and a long flight time are important, but the losses during take-off and the efficiency of the usage of the produced angular momentum during the flight are crucial as well. The results of this optimization are necessary to create effective individual techniques for quadruple jumps.